A causal model of inclusive innovation for healthcare solutions: a methodological approach to implement a new theoretical vision of social interactions and policies. Issue 2 (3rd July 2019) - Gras, Natalia; Dutrénit, Gabriela; Vera-Cruz, Matías
ABSTRACT: This paper is about knowledge production and its application to healthcare solutions oriented towards underprivileged people. Based on the existing literature, we use a different lens to approach the agents, interactions and policies related to the creation, adoption and diffusion of inclusive innovation. We propose a theoretical causal model with which conceptual and practical problems with regard to innovative and inclusive healthcare solutions could be analyzed and assessed, and discuss how public policy could contribute to stimulate processes of creation, adoption and diffusion of this kind of solutions. This paper is based on a qualitative analysis of three exemplary case studies of different developing countries. This brings elements for understandings the major influences on innovative and inclusive healthcare solutions, which are presented as a theoretical model in the form of a causal graph.